Optimal dissection for transanal total mesorectal excision using modified CO2 insufflation and smoke extraction. (November 2015) - Nicholson, G.; Knol, J.; Houben, B.; Cunningham, C.; Ashraf, S.; Hompes, R.
Abstract Aim The new approach of transanal total mesorectal excision is technically challenging and demands a stable field of dissection with optimal view of anatomical landmarks. We aimed to describe and demonstrate a modification of both the insufflation of carbon dioxide and smoke evacuation, in order to optimize dissection. Method The comparison of standard insufflation to an AirSeal platform demonstrates a clear difference. This is shown in the accompanying video‐recordings. Results A more stable pneumorectum and better smoke evacuation as well as more convenient and precise dissection were achieved with the AirSeal platform. Conclusion Using the technique outlined, the operating surgeon is able to perform the surgical dissection in a stable operating environment with increased visibility compared to the standard approach.